PENGARUH PEMANFAATAN E-POS DAN KUALITAS LAYANAN JASA PENGIRIMAN TERHADAP TINGKAT LOYALITAS PARA PELANGGAN POS INDONESIA KOTA BATAM (SUATU SURVEI PADA KECAMATAN BATAM KOTA) - Hapzi Ali; Nia Ekawati (Jurnal Ilmiah Universitas Batanghari Jambi, 2012)
Post a freight services company in Indonesia. Identified some of the problems encountered in customer loyalty is the use of Information Systems Services (e-mail) may be used less well by the customers Pos Indonesia. Quality of delivery services to good use by customers Pos Indonesia. Level of loyalty among customers at Pos Indonesia perceived less loyal. Quality of delivery of services to the level of customer loyalty among the less well used by customers Pos Indonesia. The purpose of this study was to determine effect of the use of e-mail and Postal Service Quality (e-mail) to the post of customer loyalty;This research method using the method of verification or causality methods to examine the relationship between variables. The population sample of 200 people with 133 people. Research Batam attractions post office to post office customer analytics unit. The data was obtained using a questionnaire and interviewed staff and leadership post office. Analysis Method regersi use the liner regression.The use of e-mail services and quality of service delivery affect the level of customer loyalty simultaneously at Pos Indonesia. The post office in Batam Centre is less attention to the balance of services offered Pos Indonesia to the customer so that e - mail to the Loyalty influential but less than optimal.Keywords: e - Pos, service quality, and loyalty.